Seamless Wayfinding by a Deafblind Adult on an Urban College Campus: A Case Study on Wayfinding Performance, Information Preferences, and Technology Requirements - Swobodzinski, Martin; Parker, Amy T.; Wright, Julie D.; Hansen, Kyrsten; Morton, Becky (Frontiers in Education, 2021)
This article reports on an empirical evaluation of the experience, performance, and perception of a deafblind adult participant in an experimental case study on pedestrian travel in an urban environment. The case study assessed the degree of seamlessness of the wayfinding experience pertaining to routes that traverse both indoor and outdoor spaces under different modalities of technology-aided pedestrian travel. Specifically, an adult deafblind pedestrian traveler completed three indoor/outdoor routes on an urban college campus using three supplemental wayfinding support tools: a mobile application, written directions, and a tactile map. A convergent parallel mixed-methods approach was used to synthesize insights from a pre-travel questionnaire, route travel video recordings, post-travel questionnaire, and post-travel interview. Our results indicate that wayfinding performance and confidence differed considerably between the three wayfinding support tools. The tactile map afforded the most successful wayfinding and highest confidence. Wayfinding performance and confidence were lowest for the mobile application modality. The simplicity of use of a wayfinding tool is paramount for reducing cognitive load during wayfinding. In addition, information that does not match individual, user-specific information preferences and needs inhibits wayfinding performance. Current practice pertaining to the representation of digital spatial data only marginally accounts for the complexity of pedestrian human wayfinding across the gamut of visual impairment, blindness, and deafblindness. Robust orientation and mobility training and skills remain key for negotiating unexpected or adverse wayfinding situations and scenarios, irrespective of the use of a wayfinding tool. A substantial engagement of the deafblind community in both research and development is critical for achieving universal and equitable usability of mobile wayfinding technology.